Peripartum Cardiomyopathy: A Case Report - Ozlem Ece Basaran; Emine Seda Guvendag guven; Suleyman Guven (Medical Network, 2020)
Peripartum cardiomyopathy is one of the potentially life-threatening complications of pregnancy. It is characterized by symptoms of heart failure in the last months of gestation or within five months after birth. The objective of this case report was to report a case of peripartum cardiomyopathy. A 20-years-old (G1P0) pregnant woman was referred for further evaluation of heart failure in pregnancy. The patient's family and medical histories were both unremarkable. She had a 36 weeks and 2 days dichorionic diamniotic twin pregnancy. Emergency cesarean section was performed under spinal anesthesia. During the early postoperative period, the patient complaint of respiratory distress and the diagnosis of peripartum cardiomyopathy was confirmed with physical examination, laboratory and echocardiography findings. She was transferred to the cardiac intensive care unit and received supplemental oxygen, noninvasive ventilation and intravenous infusion of lidocaine. She well tailored the medical therapy and she and her babies were discharged uneventfully after 10 days of delivery. The clinicians should keep in mind the diagnosis of peripartum cardiomyopathy in young woman with twin pregnancy in third trimester who presents with symptoms of heart failure even after delivery. Emergent cardiologic evaluation and intervention must be done for this rare and potentially morbid and mortal condition. Keywords: Ejection fraction, Peripartum cardiomyopathy, Pregnancy